Meaningful Consideration? A Review of Traditional Knowledge in Environmental Decision Making - Ellis, Stephen C. (ARCTIC, 2010)
In Canada’s Northwest Territories, governments, industrial corporations, and other organizations have tried many strategies to promote the meaningful consideration of traditional knowledge in environmental decision making, acknowledging that such consideration can foster more socially egalitarian and environmentally sustainable relationships between human societies and Nature. These initiatives have taken the form of both “top-down” strategies (preparing environmental governance authorities to receive traditional knowledge) and “bottom-up” strategies (fostering the capacity of aboriginal people to bring traditional knowledge to bear in environmental decision making). Unfortunately, most of these strategies have had only marginally beneficial effects, primarily because they failed to overcome certain significant barriers. These include communication barriers, arising from the different languages and styles of expression used by traditional knowledge holders; conceptual barriers, stemming from the organizations’ difficulties in comprehending the values, practices, and context underlying traditional knowledge; and political barriers, resulting from an unwillingness to acknowledge traditional-knowledge messages that may conflict with the agendas of government or industry. Still other barriers emanate from the co-opting of traditional knowledge by non-aboriginal researchers and their institutions. These barriers help maintain a power imbalance between the practitioners of science and European-style environmental governance and the aboriginal people and their traditional knowledge. This imbalance fosters the rejection of traditional knowledge or its transformation and assimilation into Euro-Canadian ways of knowing and doing. Dans les Territoires du Nord-Ouest du Canada, les gouvernements, les sociétés industrielles et autres organisations ont essayé de nombreuses stratégies pour promouvoir une prise en considération sérieuse du savoir traditionnel dans le processus décisionnel visant l’environnement, reconnaissant ...